Comparative Study on Life Cycle CO2 Emissions from the Production of Electric and Conventional Vehicles in China. (May 2017) - Qiao, Qinyu; Zhao, Fuquan; Liu, Zongwei; Jiang, Shuhua; Hao, Han
Abstract: Electric Vehicles (EVs), as expected to help save energy and reduce CO2 emissions, are facing a rapid growth in China, the country with approximately one quarter of global vehicle production. However, the ability of EVs is estimated mainly on the basis of use phase, which is not complete enough. Aiming to identify the real ability of EVs in China, this study estimates the CO2 emissions from production phase and compares the results with the level of Internal Combustion Engine Vehicles (ICEVs), the current dominating vehicles in China. The results reveal that the CO2 emissions from the production of an EV range from 14.6 to 14.7 t, 59% to 60% higher than the level of an ICEV, 9.2 t. The Li-ion batteries and additional components such as the traction motor and electronic controller in an EV are the major reasons, while different curb weights and different composition between these two vehicles contribute as well. As the manufacture techniques of Li-ion batteries are growing and the material recycle industry is developing, huge reduction potential of CO2 emissions from EVs exists in China.